Molecular details of CIP2A-B56γ1 protein interaction - Kullberg, Nora (My University, 2024)
Protein phosphatases and kinases are a crucial part of cellular signalling. Protein phosphatase 2A (PP2A) is a major serine/threonine phosphatase. The PP2A holoenzyme has three subunits: scaffolding A, regulatory B and catalytic C subunit. The regulatory B subunits determine the protein’s function. Human B subunits can be divided into four families: B55, B56, B72 and striatin. PP2A is a tumor suppressor, and it is inhibited in cancer mostly by non-genetic mechanisms. These mechanisms include post-translational modification and inhibition by PP2A inhibitor proteins such as cancerous inhibitor of PP2A (CIP2A). CIP2A is an oncoprotein and its expression levels in normal tissues are low except in the testis. High expression levels of CIP2A have been reported in multiple cancer types. CIP2A binds to B56 subunits, and this way prevents A subunit from binding to B and C subunits. Further, by binding to B56 proteins CIP2A blocks the substrate binding pocket of B56. As CIP2A inhibits PP2A, the inhibition of CIP2A could be a therapeutical target. N-terminal (1-560) fragment of CIP2A has been successfully crystallized and it interacts with B56α and B56γ proteins. Shorter N-terminal fragments of CIP2A have also been shown to interact with B56 proteins. The aim of this project was to find out what is the shortest N-terminal fragment of CIP2A that can bind and could be co-crystallized with B56γ1. The used CIP2A fragments were CIP2A(1-560), (1-330), (1-159) and (1-40). All recombinant proteins were produced bacterially. Binding assays were conducted with microscale thermophoresis (MST) where fluorescent labelled proteins move directly through a microscopic temperature gradient. Changes in protein properties such as size and charge affect its movement through the temperature gradient. With MST we were able to prove that CIP2A(1-159) binds to B56γ1. CIP2A(1-560) binding to B56γ1 was used as a positive control. CIP2A(1-330) was also able to bind to B56γ1. Protein crystallization assays were set up with CIP2A(1-330)-B56γ1 and CIP2A(1-159)-B56γ1 complexes, and crystal screening produced two crystals. One crystal was a salt crystal, and no data collection has been done with the second crystal. Next step in this research would be to continue crystal screening and to test other methods for structural determination of the CIP2A-B56γ1 complex.
Keywords: CIP2A, microscale thermophoresis, protein crystallization, protein-protein interactions, protein phosphatases, PP2A